Perilaku Manajemen Keuangan Pribadi : Peran E-Wallet, Self-Control, dan Pendapatan - Masitah, Umi; Maslichah, Maslichah; Fakhriyyah, Dewi Diah (e_Jurnal Ilmiah Riset Akuntansi, 2026)
This study aims to examine the effect of financial technology (e-wallet) and self-control on students’ personal financial management behavior, with income as a moderating variable. The rapid development of e-wallet services offers convenience and efficiency in financial transactions, but it may also influence individuals’ financial management patterns, particularly among university students. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 86 students of the Faculty of Economics and Business, Universitas Islam Malang, class of 2022, who had used or were currently using e-wallet services. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results indicate that financial technology (e-wallet) and self-control have a positive and significant effect on personal financial management behavior. Income also has a direct positive effect on financial management behavior. However, income does not moderate the relationship between financial technology or self-control and personal financial management behavior. These findings suggest that students’ financial management behavior is more strongly influenced by behavioral and psychological factors rather than differences in income levels, which tend to be relatively homogeneous. This study contributes empirically to the literature on students’ financial behavior in the digital era and provides practical implications for improving financial literacy and self-control.Keywords: Financial technology; e-wallet; self-control; income; personal financial management behavior